Endoplasmic reticulum aminopeptidase 1 and rheumatic disease: functional variation. Issue 4 (July 2015) - Tran, Tri M.; Colbert, Robert A.
Abstract : Purpose of review: To review the recent developments in our understanding of endoplasmic reticulum (ER) aminopeptidase 1 (ERAP1) function in relation to its role in major histocompatibility complex (MHC) class I peptide presentation and human leukocyte antigen (HLA) class I-associated diseases. Recent findings: ERAP1 polymorphisms exhibiting loss-of-function have been associated with protection from AS. The aminopeptidase function of ERAP1 optimizes peptides for binding and presentation by MHC class I. Most of the studies have revealed reduced MHC class I expression in situations of reduced ERAP1 function. Under these circumstances, the presented peptides are often N-terminally extended, and cell surface complexes are unstable and fall apart more readily. In contrast, peptides presented by HLA-B*27 : 05 when ERAP1 is silenced are frequently extended on the C-terminus. Recent work has emphasized on the importance of assessing the function of allotypes encoded by ERAP1 haplotypes, rather than effects of single amino acid substitutions. The allotypes found in a series of AS patients were poorer at restoring HLA-B27 expression than allotypes found in unaffected controls, which may seem contrary to the genetic data linking loss-of-function to protection. Summary: More work is needed to understand how ERAP1 variants associated with risk and protection influence the quality and quantity of peptides available for binding to HLA class I molecules in the ER. Moreover, we need to determine allele-specific effects of ERAP1 variants in the context of HLA-B*51 and HLA-Cw*6, which are associated with Behçet's disease and psoriasis, respectively.